A Case Study on a Translation of a Defective Source Text - Taufan, Gullit Tornado; Ismailia, Titik; Pramudita , Rizqi Febrian; Suharsono, Degita Danur (Journal of Language, Communication, and Tourism, 2024)
Translating defective or flawed source texts can be very challenging for translators. Defective texts are often characterized by spelling and grammatical errors, inappropriate uses of punctuations, unclear messages and expressions, incomplete and ambiguous information, etc. In translation such texts require careful analysis that may lead to corrections and revisions of the source texts before the translation process occurs. This case study highlights how a translator handled defective source texts, in this case a tourism booklet. The aim of the study was to investigate the errors found in the booklet, how the translator dealt with the challenges, and how the defective text influenced the whole process of the translation. The findings show that the errors found were structural and substantial ones, the translator needed to undergo several strategies to handle solve the problems, and the defective source text influenced the overall process of the translation especially in the initial step.